Hypothalamic metabolic compartmentation during appetite regulation as revealed by magnetic resonance imaging and spectroscopy methods - Lizarbe, Blanca; Benítez, Ania; Peláez, Gerardo A.; Sánchez-Montañés, Manuel; López-Larrubia, Pilar; Ballesteros, Paloma; Cerdan, Sebastian (Frontiers in Neuroenergetics, 2013)
We review the role of neuroglial compartmentation and transcellular neurotransmitter cycling during hypothalamic appetite regulation as detected by Magnetic Resonance Imaging (MRI) and Spectroscopy (MRS) methods. We address first the neurochemical basis of neuroendocrine regulation in the hypothalamus and the orexigenic and anorexigenic feed-back loops that control appetite. Then we examine the main Magnetic Resonance Imaging and Spectroscopy strategies that have been used to investigate appetite regulation. Manganese enhanced magnetic resonance imaging (MEMRI), Blood oxygenation level dependent contrast (BOLD) and Diffusion weighted magnetic resonance imaging (DWI) have revealed Mn2+accumulations, augmented oxygen consumptions and astrocytic swelling in the hypothalamus under fasting conditions, respectively. High field 1H magnetic resonance in vivo, showed increased hypothalamic myo-inositol concentrations as compared to other cerebral structures. 1H and 13C high resolution magic angle spinning (HRMAS) revealed increased neuroglial oxidative and glycolytic metabolism, as well as increased hypothalamic glutamatergic and GABAergic neurotransmissions under orexigenic stimulation. We propose here an integrative interpretation of all these findings suggesting that the neuroendocrine regulation of appetite is supported by important ionic and metabolic transcellular fluxes which begin at the tripartite orexigenic clefts and become extended spatially in the hypothalamus through astrocytic networks, becoming eventually MRI and MRS detectable.